Fructose-enriched diet affects hepatic lipid metabolism in young male and female rats in different ways - Brkljačić, Jelena; Veličković, Nataša; Elaković, Ivana; Teofilović, Ana; Vojnović Milutinović, Danijela; Đorđević, Ana; Matić, Gordana (Archives of Biological Sciences, 2019)
Abstract: An increase in fructose consumption coincides with a rising incidence of metabolic disorders. Dietary fructose has been shown to affect hepatic lipid metabolism in a way that may lead to lipid deposition in the liver. In this study, we tested the hypothesis that the effects of fructose overconsumption on hepatic lipid metabolism differ between sexes. To that end we examined the effects of a high-fructose diet on the expression of key enzymes and transcription factors involved in the regulation of fatty acid oxidation and de novo lipogenesis in the liver of 12-week-old male and female Wistar rats. Immediately after weaning, the rats were subjected to a standard diet and 10% fructose solution or drinking water for 9 weeks. The fructose-enriched diet induced hypertriglyceridemia and increased hepatic de novo lipogenesis in both sexes, without lipid deposition in the liver. At the same time, visceral adiposity was observed only in female rats, while in males the treatment stimulated hepatic fatty acid oxidation. The fructose-enriched diet induced sex-specific effects on hepatic lipid metabolism in young rats. These results imply that male and female rats employ different strategies to cope with dietary fructose-related energy overload and to avoid lipid accumulation in the liver. https://doi.org/10.2298/ABS190306023N Received: March 6, 2019; Revised: April 2, 2019; Accepted: April 2, 2019; Published online: April 9, 2019 How to cite this article: Brkljačić J, Veličković N, Elaković I, Teofilović A, Vojnović-Milutinović D, Đorđević A, Matić G. Fructose-enriched diet affects hepatic lipid metabolism in young male and female rats in different ways. Arch Biol Sci. 2019;71(3):417-24.